Revisited stress-dependent curie-temperature in BCC iron: LSDA+U cleansing of magnon ambiguities - Kanokwan Kanchiang (2018)
This study proposes that the strong correlation of the 3d electrons in Fe is an important key to understanding the stress dependence behavior of Curie temperature (TJ. We proved our proposed hypothesis using density functional theory (DFT) within an LSDA+U (local spin density approximation +U) framework. Applying LSDA+U correction increased both the magnetic moment and magnon energy. The increased magnon energy directly contributed to the higher magnitude of the calculated Tc(compared with LSDA). The acquired Tc(from LSDA and LSDA+U) decreased with increasing unit cell volume; this was consistent with previous studies. Although introducing an on-site Coulomb interaction yielded the same stress dependence trend of Tccompared with the LSDA results, increasing the Tcmagnitude was more reasonable under mean-field approximation, suggesting that the strong interaction of the 3d electrons in Fe influenced this phenomenon.